(untitled) (Global Journal of Science Frontier Research, 2018)
Thermal comfort is an essential element for the human body and is increasingly becoming a crucial factor to be considered in footwear design. The previous study has shown that thermal conditions play a dominant role in-shoe climate. Development of thermal models that are capable of predicting in-shoe temperature distributions is an effective way to assist in design optimization. The aim of this study was to analyse the distribution of temperature, and the level of thermal comfort during wear of footwear through predicted mean vote (PMV) & percentage person’s dissatisfaction (PPD) model using computational fluid dynamics (CFD) techniques. These will make easier to approximate the heat transferthermal-comfort relationships among the components. Four different temperatures ranges from very cold to very hot such as -20°C, 7°C,40°C,50°C were considered for this analysis,. The occupant (human foot) felt neutral to slightly cool in the cold weather and felt very hot in the hot weather within the footwear, and their PPD is more than 25%, 24%, 99.1%, and 99.1% respectively that means 74-75% persons will be satisfied in the cold and only of 0.99% persons will be satisfied in the hot country. Thus from this study, it can be concluded that the effectiveness of the footwear design for keeping the human foot thermally comfortable for different variety of weather can be assessed through this technique of CFD simulation.